(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. High frequency welding — a new electrosurgical method which is based on the influence of an electric current with a frequency of 66 kHz on biological tissue with the possibility of connection of different types of tissues with minimal coagulation changes. Purpose. Investigation of morphological changes of chorioretinal complex in rabbits in remote terms after exposure to high-frequency electric current with a frequency of 66 kHz (modified generator PC — 300M1). Material and methods. The study was performed on 18 rabbits (36 eyes), which were divided into 2 groups. The first group performed the welding of chorioretinal complex with high-frequency electric current parameters: frequency — 66 kHz, voltage — 14—16 V, current — 0.1 A. The second group of welding took place at the level of electrical voltage 18—20 V. The experimental animals derived from experiment 3, 7 day and 1 month after surgery. Morphological studies performed by light microscopy. Results. After 3—7 days after exposure of high-frequency electric current with a frequency of 66 kHz at 14—16 V voltage levels significant structural changes occur mainly at the level of the outer layers of the retina, characterized by homogenization photoreceptors, the destruction of the apical cell surface of retinal pigment epithelium, and of edema outer nuclear layer. After 1 month of change in thickness and architectonics layers of the retina were minimal and only kept on the edge of welding applications. Some destructive changes were recorded in the layer of photoreceptors and retinal pigment epithelium with formation of chorioretinal scar. Under the influence of high-frequency electric current with a frequency of 66 kHz at 18—20 Vvoltage on day 3 were recorded destructive changes in all layers of the retina. After 7 days, partially renewed architectonic of nuclear layers, but the number of neurons is reduced. After 1 month marked thinning of all layers of the retina and proliferation of connective tissue cells at the level of the pigment epithelium, neuroepithelium and choroid, but the area of scarring was significantly higher than in animals of the first group. Conclusion. Effect of high-frequency electric current with a frequency of 66kHz (modified generator EC — 300M1) at 14—16 Vvoltage levels accompanied by destructive changes mainly the outer layers of the retina in the first 7days, followed by the formation of chorioretinal scar just on the edge of welding applications. When the voltage level of 18—20 degree increases coagulation changes and they cover all layers of the retina. The area of chorioretinal scarring in terms of 1 month is significantly higher.